The Little Green Data Book 2007 - World Bank (World Development Indicators, 2007)
This pocket-sized reference on key environmental data for over 200 countries includes key indicators on agriculture, forestry, biodiversity, energy, emission and pollution, and water and sanitation. The volume helps establish a sound base of information to help set priorities and measure progress toward environmental sustainability goals